Practice patterns in the use of prophylactic antibiotics following nonoperative orbital fractures - Wang JJ (Dove Medical Press, 2016)
Jijo Jizhou Wang,1 Jennifer M Koterwas,2 Edward H Bedrossian Jr,2 William J Foster2,3 1Lewis Katz School of Medicine, 2Department of Ophthalmology, Lewis Katz School of Medicine, 3Department of Bioengineering, College of Engineering, Temple University, Philadelphia, PA, USA Purpose: The purpose of this study was to analyze the practice management patterns of the current members of the American Society of Ophthalmic Plastic and Reconstructive Surgery (ASOPRS) and to determine the use of oral prophylactic antibiotics in an attempt to prevent orbital cellulitis following nonoperative orbital fractures.Patients and methods: A cross-sectional web-based survey was emailed to all the members of ASOPRS regarding their current management of nonsurgical orbital fractures and their experience with orbital cellulitis following nonoperative orbital fractures.Results: The majority of practicing oculoplastic surgeon members of ASOPRS do not routinely prescribe prophylactic antibiotics for patients with nonoperative orbital fractures or patients with orbital fractures whom the physicians are observing and who might potentially need surgical intervention. Among the reported cases of orbital cellulitis following a nonoperative orbital fracture in this survey, more than a quarter of the patients had received prophylactic antibiotics. Furthermore, among physicians who have managed orbital cellulitis following nonoperative fracture, 75% (33 out of 44 physicians) report that <1% of patients develop orbital cellulitis.Conclusion: Despite frequent recommendation for the use of prophylactic antibiotics after orbital fractures in commonly cited ophthalmic references, the majority of oculoplastic surgeons do not use prophylactic antibiotics for orbital fractures, including both nonoperative orbital fractures and orbital fractures that may potentially need surgery. Keywords: orbital blowout fracture, orbital fracture, antibiotic use, practice patterns, survey